RADIOGRAPHIC EXAMINATION PROCEDURE AS NON DESTRUCTIVE TESTING METHOD IN PROCESS PIPING - Rachmasari Pramita wardhani (Mechanical Engineering Departement - Universitas Tridharma, 2019)
Industry must have good quality for their services or products. One of the things that their have done is how to get the customer’s belief in their brand. Quality in every part has become the main case. Most of the companies in industry use metals as material to support their services. When the goods have been processed, it must continue with the testing. This is to prove that the goods have gone through the formation process fill in standard quality which required by the customer. There are two types of testing known as destructive testing and non-destructive testing. There are some of ways of non destructive testing methods on metals inspection has been applied in testing the quality of goods. Such as visual test, magnetic particle test, liquid penetrant, eddy current test, ultrasonic test, radiographic test in metals testing. Nondestructive testing (NDT) is the process of inspecting, testing, or evaluating materials, components or assemblies for discontinuities, or differences in characteristics without destroying the serviceability of the part or system. Radiographic Testing (RT) is a nondestructive examination technique that involves the use of either x-rays or gamma rays to view the internal structure of a component. In the petrochemical industry, Radiographic Testing is often used to inspect machinery, such as pressure vessels and valves, to detect for flaws. RT is also used to inspect weld repairs. Compared to other NDT techniques, radiography has several advantages. It is highly reproducible, can be used on a variety of materials, and the data gathered can be stored for later analysis. Keywords—radiographic, non-destructive testing, piping, examination